Legal aspects of state administration in the field of water conservation and rehabilitation of water resources - Соколова, А. К. (Problems of legality, 2015)
This research is dedicated to issues, related to determining the legal principles of management in the sphere of water protection, use and rehabilitation of water resources. It considers the legislative acts, determining competences of the related state authorities. The research provides recommendations on improving appropriate legislation.